Seasons influence on content, yield and chemical composition of Origanum majorana L. essential oil - de Souza, Jéssica Maronez; Cargnelutti Filho, Alberto; Carini, Fernanda; da Costa, Samanta Luiza; Heinzmann, Berta Maria; Rodrigues, Patrícia (Comunicata Scientiae, 2021)
The aim of this study was to determine the season that provides the highest production and best quality of marjoram (Origanum majorana L.) essential oil in summer and winter transplants. Two experiments were performed in a protected cultivation, the first with transplantation in summer and the second with transplantation in winter, with a completely randomized design with four treatments, being the seasons of the year. Content, yield and chemical composition of the essential oil were determined. The essential oil was extracted by hydrodistillation and analyzed by gas chromatography. In the summer transplant the essential oil content and yield were higher in the summer and spring seasons. In the winter transplant the oil content was higher in the summer season and the yield in the summer and in spring. Carvacrol was the major component of marjoram essential oil regardless of harvest and transplant season. Of the other main compounds, only terpinolene was detected in all samples analyzed, with the other essential oil components varying between transplant and harvest seasons. The highest production of marjoram essential oil is obtained in summer and spring harvests from plants transplanted in summer and winter. The major components of marjoram essential oil are carvacrol and terpinolene.